Malignant Arrhythmia and Cardiac Arrest Following Intentional Yew Tree Leaf Ingestion Salvaged by VA‐ECMO - William Ries; Muhammad Faisal; Thomas Kirk; Aqib Hafeez; Laura Vincent; David Clarke; Graham Barker (Clinical Case Reports)
ABSTRACT This case emphasizes the role of multidisciplinary involvement and early decision‐making in yew tree (Taxus baccata) poisoning. Taxus baccata contains taxine alkaloids that predispose to malignant arrhythmia. Here, we present a case of Taxus baccata toxicity presenting with refractory cardiac arrest, salvaged ultimately by VA‐ECMO.